Diagnóstico de resistência anti-helmíntica em bovinos - Neves, José Henrique das [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The anthelmintic resistance in cattle has become a global problem, and in Brazil it has been reported in some states. Due to the need for more accurate methods of diagnosis of anthelmintic resistance the purpose this work was to evaluate two techniques (McMaster and Flotac) and two mathematical formulas (FECRT1 - according to the average EPG and FECRT2 - according to the total number of eggs counted) to calculate the faecal egg count reduction test (FECRT) in the diagnosis of anthelmintic resistance in cattle. The anthelmintic tested were ivermectin (0.2 mg/kg), moxidectin (0.2 mg/kg), albendazole sulfoxide (2.5 mg/kg) and levamisole phosphate (4.7 mg/kg), administered at the dose recommended by the manufacturer. Ten farms were assessed, four visits in each pre-treatment (D -2), processing (D 0), 10 days post-treatment (D 10) and 28 days post-treatment (D 28). In all of the properties was observed resistance to one or more anthelmintics tested, regardless of the technique (McMaster or Flotac) or FECRT the mathematical formula (1 and 2). The genera/species found with resistance to one or more anthelmintics were Haemonchus placei, Cooperia spp., Trichostrongylus spp. and Oesophagostomum radiatum. In conclusion, the anthelmintic resistance is present in all herds evaluated. The Flotac technical and mathematical formula FECR2 were more accurate than the McMaster technique and formula FECR1. Need is greater awareness of the producers on the use of anthelmintics. Therefore, in future studies on anthelmintic resistance in cattle, use of the method of diagnosis with higher accuracy, it is recommended, as is the case FLOTAC method. In interpreting the results, our study indicates that the calculation by formula FECR2 %, which eliminates the use of a control group, should be recommended

A resistência anti-helmíntica em bovinos se tornou um problema global, e no Brasil tem sido relatada em alguns estados. Devido à necessidade de métodos mais precisos de diagnóstico da resistência anti-helmíntico, o objetivo deste trabalho foi avaliar duas técnicas (McMaster e Flotac) e duas fórmulas matemáticas (FECRT1 - de acordo com a média de OPG e FECRT2 - de acordo com o número total de ovos contados) para calcular o teste de redução de ovos nas fezes (FECRT). O anti-helmíntico testados foram ivermectina (0,2 mg/kg), moxidectina (0,2 mg/kg) , sulfóxido de albendazol (2,5 mg/kg) e fosfato de levamisol (4,7 mg/kg) , administrada na dose recomendada pelo fabricante. Dez propriedades foram avaliadas, quatro visitas em cada, pré-tratamento (D - 2), processamento (D 0), 10 dias pós-tratamento (D10) e 28 dias póstratamento (D28). Em todas as propriedades foi observada resistência a um ou mais agentes anti-helmínticos testados, independentemente da técnica ou da fórmula matemática avaliada. Os gêneros/espécies encontradas com resistência a um ou mais anti-helmínticos foram Haemonchus placei, Cooperia spp., Trichostrongylus spp. e Oesophagostomum radiatum. Em conclusão, a resistência anti-helmíntica está presente em todos os rebanhos avaliados. A técnica Flotac e a fórmula matemática FECR2 foram mais precisas do que a técnica de McMaster e fórmula FECR1. Há necessidade de maior conscientização dos produtores sobre o uso de anti-helmínticos. Portanto, em estudos futuros de resistência anti-helmíntica em bovinos, recomenda-se a utilização do método de diagnóstico com uma maior precisão, como é o método Flotac. Na interpretação dos resultados, nosso estudo indica que o cálculo pela fórmula FECR2, o que elimina o uso de um grupo de controle, deve ser recomendada
Keywords: Helminto; Bovino - Parasito; Intestinos - Infecções; Drogas - Resistencia; Intestines Infections